Pelatihan Buzz Marketing Pada Sepatu Adidas - Bambang Hengky Rainanto; Febri Damatraseta; Rafli Pradana (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
Buzz Marketing or word of mouth is an important attribute of Buzz Marketing. There are four attributes in Brand Equality from Brand Awareness , namely Association Brand ,, apartPrecieved Quality (perceived quality), Brand Loyalty (Brand Loyalty) and Other Proprientary Brand Assets (brand assets). other). There are four levels in Buzz Marketing, namely: Top Of Mind , Brand Recall , Brand Recognition , and Unware of Brand . In this review, it only focuses on